American English pronunciation program - Raifsnaider, Barbara; Warnasch, Christopher A. (New York Living Language, 1999)
An audio program that teaches standard American pronunciation with examples of words, phrases, full sentences, and rapid conversational English.
For speakers of English as a second language and native speakers with strong regional accents.
Keywords: English language -- Pronunciation. -- United States; English language -- Pronunciation